1995
DOI: 10.2307/2135972
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Substance Use to Sexual Activity Among Young Adults in the United States

Abstract: Data on substance use and sexual activity from a nationally representative, probability-based sample of young adults aged 18-30 in 1990 indicate that 86% of respondents had had sex in the previous 12 months, with three-fourths reporting no more than one sexual partner. Seventy-five percent of respondents had consumed alcohol in the past 12 months, 40% had smoked cigarettes and 20% had used marijuana. After adjustment for demographic factors, both sexual activity and a history of multiple partners were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 28 publications
5
88
2
Order By: Relevance
“…These results echo other findings elucidating adolescents' reasons for condom non-use 36 but are notably contrary to those from previous quantitative studies of adolescents, which indicate no association between condom use and substance use at last sex. 37,38 Lack of consistency between present findings and this previous work may be indicative of major differences in sampling and data collection methods, or it may a consequence of previous studies assessing solely risk at last sex. More research is needed to better elucidate the associations between substance use and sexual risk among adolescent male perpetrators of dating violence.…”
Section: Discussioncontrasting
confidence: 43%
“…These results echo other findings elucidating adolescents' reasons for condom non-use 36 but are notably contrary to those from previous quantitative studies of adolescents, which indicate no association between condom use and substance use at last sex. 37,38 Lack of consistency between present findings and this previous work may be indicative of major differences in sampling and data collection methods, or it may a consequence of previous studies assessing solely risk at last sex. More research is needed to better elucidate the associations between substance use and sexual risk among adolescent male perpetrators of dating violence.…”
Section: Discussioncontrasting
confidence: 43%
“…Gold et al (1992) found that the level of intoxication reported on two different sexual encounters was associated with whether the respondent had engaged in unprotected sex during those encounters. Graves and Leigh (1995) found no significant relationship between intoxication and unprotected sex when they compared the proportion of unprotected sexual encounters under the influence of alcohol vs. those without alcohol, even though they noted a global association between heavy-drinking and unprotected sex. In a probability sample of the adult household population of a county in the San Francisco Bay Area, Temple and Leigh (1992) reported that drinking at the most recent reported sex encounter was either not related to unprotected sex (among women) or was associated with a decreased likelihood of unprotected sex (among men).…”
mentioning
confidence: 94%
“…Drug use is a determinant of high-risk behavior and infection, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and substantial proportions of the US prison population report a history of heavy drug and alcohol use. 48 The effect of incarceration on STI/HIV risk may differ by drug use status.…”
mentioning
confidence: 99%